E – Katalog Official Honne Payakumbuh - Monica Kirana Utomo; Eliya Pebriyeni (Lembaga Pengembangan Kinerja Dosen, 2023)
Official Honne is a fashion brand that sells Muslim fashion products such as dresses and hijabs which was pioneered by Azzahra Sukma Rusita. This Muslim fashion brand was founded in 2019 which is located in Payakumbuh. The Muslim fashion products produced by Honne are limited edition products that are not widely available on the market with elegant and luxurious designs created by the owner making these products in great demand by Muslim consumers. Official Honne does not yet have a promotion that contains complete product information. After conducting an interview with the owner of the Official Honne, the owner of the Official Honne business finds it very helpful if there is an attractive promotion for the products offered by Honne. Seeing the business conditions of Official Honne which have been established since 2019, it is necessary to design attractive and appropriate promotional media and information to promote Official Honne Muslim fashion products.